Column and beam construction projects at Alor Lintang, Mukim Kampung Raja, Daerah Besut, Terengganu Darul Iman / Arif Ismail - Ismail, Arif (Universiti Teknologi Mara, Perak, 2015)
Generally, this practical training report clarifies the information about all of the works, processes and methods on the construction of the column for Project Hamzah Bin Mohd Yusof at Alor Lintang, Besut, Terengganu. This practical training report is prepared based site visit at the construction site. This practical training report is started with explanation and clarification of company background and background of project. The construction of column isn’t as easy as it seen. This construction need to focus because if any collapse during the construction, our company will fully responsible to the failure. The inspection must follow the drawing that have been design and all the specification and what have been include in the drawing must be follow to avoid from the failure after the construction. As the conclusion, this practical training report can explain in details about the construction column and beam.